Study of Generalized Hourglass Section in Carbon Nanocone via Connection Number. (3rd August 2021) - Mubashar, Muhammad; Hussain, Muhammad; Abdulrahman Alrawajeh, Fatimah; Almotairi, Sultan
Abstract : In 1972, Gutman and Trinajstic showed that total π -energy of a molecule depends upon a numeric quantity which is often called as Zagreb index. In the same report, they also discussed another numeric quantity depending on the number of atoms at a distance two from a particular atom and proved influencing results on π -energy of a molecule. In modern literature, this quantity is named as connection number. In this article, we will describe some Zagreb connection numbers for hourglass section in carbon nanocone network with different lengths of cycle in the central core.